Pengaruh Fasilitas, Transportasi Dan Akomodasi Terhadap Kepuasan Wisatawan Dikabupaten Semarang - Nunuk Supraptini; Andhi Supriyadi (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2020)
Tourism in Semarang district growth by availability of facilities, transportation and accommodation in every tourism objects. To fulfill satisfaction of traveller and to invite more of traveller, tree of the variable were needed. This research discussed the effects of facilities, transportation and accommodation to satisfy of traveller. Kottler (2005) facility is physically equipment which provided by service seller to customer’s comfortable. Fidel Miro (2005) transportation is to move or shift object from one to other location by transportation equipment and accommodation is goods which provided to fulfill someone need while traveller. This research do descriptive quantitative on associative research. There 100 of traveller be respondents, used questioner to collect data. Validity and reliability test use as instruments test. Simple correlation and multiple, simple linear regression and multiple, determination (adjusted R square) t test and F test used for analytical technique. The Result show that facilities, transportation and accommodation able to descript of tourism satisfaction on tourism object at Semarang district. By t test of facilities, transportation and accommodation positively effect and significant to tourism satisfaction. By F test shown that facilities, transportation and accommodation positively effect to tourism satisfaction